Bio-psycho-social-spiritual responses of family and relatives of HIV-Infected Indonesian Migrant Workers - Nursalam Nursalam; Ninuk Dian Kurniawati; Abu Bakar; Purwaningsih Purwaningsih; Candra Panji Asmoro (Universitas Airlangga, 2014)
Introduction: Incidence of Human Immunodeficiency Virus (HIV) among Indonesian Migrant Workers (TKI) returning from his destination countries, especially in East Java is quite high. Stress experienced by the patient is affected bythe family member maladaptive behaviors; thus affect healing process and even increased mortality. The purpose of this study was to analyze the response of the bio-psycho-socio-spiritual family of Indonesian Workers who are infected with HIV and compared with the response of non-family workers who are infected with HIV.Method: Research design was comparative to reveal the response of the bio-psycho-socio-spiritual families of HIV-infected familyof migrant workers and non-migrant workers. The population was family of both migrant and non-migrant in two districts in East Java in 2014. Sample of 17 people were recruited by simple random sampling technique. Data were performed at the family home, including biologic response (venous blood sampling for cortisol examination), and measurement of the psychological, social and responses by using questionnaires and interviews. Data were analysed with statistical t test and Mann-Whitney test with a significance level of 0.05.Result: The results showed no differences in the biological response of HIV patients’ families among migrant and non-migrant workers (p = 0.000) although the majority of respondents were in the normal range or not stress. In contrast, the psychology, social and spiritual responsesshowed no statistically significant difference with p = 0.065, p = 0.057, p = 0.243 for psychological, social, and spiritual responses respectively.Discussion: There is a difference in the biological response (cortisol) in the group of family and relatives of patients with HIV among migrant workers compared with non-migrant workers, but there is no statistical difference in the psychological, social and spiritualresponses.